Gestural Ways of Depicting Metaphors and Abstract Concepts - Kraśnicka Izabela (Studies in Logic, Grammar and Rhetoric)
The aim of the article is to present ways in which gestures combine with the verbal layer of an utterance, thus reflecting embodied thinking and the rooting of abstract concepts in human bodily experience. The article discusses two different ways in which gestures, described in the literature as metaphoric, illustrate both linguistically expressed metaphors and abstract concepts that are not verbally expressed as metaphors. The data analyzed in this paper have been taken from speeches of politicians and other public figures.